2018
DOI: 10.1017/s0890060418000082
|View full text |Cite
|
Sign up to set email alerts
|

A computational tool for creative idea generation based on analogical reasoning and ontology

Abstract: Analogy is a core cognition process used to produce inferences as well as new ideas using previous knowledge and experience. Ontology is a formal representation of a set of domain concepts and their relationships. The use of analogy and ontology in design activities to support design creativity have previously been explored. This paper explores an approach to construct ontologies with sufficient richness and coverage to support reasoning over real-world datasets for prompting creative idea generation. This app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 131 publications
(179 reference statements)
0
44
0
Order By: Relevance
“…It is based on the analysis of 2.5 million patents and the formalization of them into some patterns of thinking process. Han et al (2018) developed a computational tool called "the Retriever" which has a knowledge database of patterns of analogical thinking. It can help designers produce creative ideas through design space expansion and exploration.…”
Section: Prior Work Of Design Concept Generationmentioning
confidence: 99%
“…It is based on the analysis of 2.5 million patents and the formalization of them into some patterns of thinking process. Han et al (2018) developed a computational tool called "the Retriever" which has a knowledge database of patterns of analogical thinking. It can help designers produce creative ideas through design space expansion and exploration.…”
Section: Prior Work Of Design Concept Generationmentioning
confidence: 99%
“…Han et al . (2018) carried out a design experiment involving 20 participants to produce ideas for a design challenge with and without the Retriever, which is a computational tool developed by the authors to assist idea generation. Their experiment recorded and evaluated the performance of participants based on four matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Chiu and Shu (2012) claimed that creative concepts often lead to creative and successful designs. Han et al (2018a) suggested creativity is linked to economic benefit via design. Sarkar and Chakrabarti (2011) indicated that creativity is crucial for business portfolios and designing products, as it initiates innovations, supports problem-solving, and is closely associated with market share.…”
Section: Introductionmentioning
confidence: 99%